Distribución de la cotorra argentina (Myiopsitta monachus) en la ciudad de Durango, México - Rodríguez-Maturino, Alberto; Fernández-García, Jorge Alberto; Viggers-Carrasco, María Guadalupe; Gómez-Espinoza, Aurora; Ríos-Gurrola, Mónica Gabriela; Arenivas-Villa, Deissy Elizabeth; Guerrero-Guerrero, Emmanuel Antonio (Instituto de Ecología, A.C., 2018)
We report for the first time the presence of the Monk Parakeet (Myiopsitta monachus) in urban areas and on the periphery of the Durango city, Mexico. There were six nesting sites on five different plant species; one place was located close to natural vegetation.